Clinical Characteristics of 33 Asymptomatic COVID-19 Infections in Wuhan, China - Yuanyuan Chen; Xiaoping Chen; Linwei Wang; Ruiying Zheng (Journal of Infection in Developing Countries)
Clinical characteristics of 33 asymptomatic COVID-19 infections were analyzed in this study. The data showed most of asymptomatic patients had small body mass index, good prognosis and low infectivity. This study suggests that screening from high-risk populations to find and isolate asymptomatic patients is an important disease prevention and control strategy for COVID-19.